Peningkatan Hasil Belajar Siswa dengan Sikap Kritis Materi Sifat-Sifat Gereja Melalui Model Problem Based Learning (PBL) pada Siswa Kelas XI Fase F SMK Negeri 1 Lahomi Kabupaten Nias Barat - Salvinus Sonifati Daeli (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Study This aiming For increase results Study student eye lesson Catholic Religious Education and Character​ through the Problem Based Learning model . Research action class This implemented as many as 2 cycles with four stages namely : planning, implementation, observation, reflection. Subject study This is student Class XI of State Vocational School 1 Lahomi as many as 6 students. Research This use technique analysis descriptive qualitative . Indicator action study This is a learning system finished namely achievement KKM value ≥75. Success Study measured if every student has reach value ≥75 then it is said succeed finished And in a way classical if as many as 80% of students has reach value ≥75 then it is said finished in a way classical. Problems in study This is lack of activity student For Study especially on moment do questions practice , difficulty student understand material the lesson in progress discussed , students not enough brave disclose opinion And Not yet capable think critical. For minimize problem said, researchers carry out study action class with objective For know improvement results Study student on eye lesson Catholic Religious Education and Character​ with material main Properties Church on class XI phase F SMK 1 Lahomi Regency West Nias Year 2024/2025 lessons through problem based learning model . Based on test results learning gained​ on end cycle I with average results Study student of 16.67 with percentage completeness which is 33.34%. Meanwhile test results Study on cycle II experienced significant improvement​ with average results obtained Study of 98.33 with percentage completeness namely 98.33% with category proficient . With thus, then can concluded that improvement results Study student with attitude critical material properties Church through the problem based learning (PBL) model student class XI phase F SMK 1 Lahomi regency West Nias Year 2024/2025 learning results change Study students who can proven with achievement Criteria Minimum Completion Criteria (KKM) that has been achieved set .